A Capacitive DC-DC Boost Converter with Gate Bias Boosting and Dynamic Body Biasing for an RF Energy Harvesting System - Jiho Jung; Ickjin Kwon (Sensors, 2022)
In this paper, a fully integrated capacitive DC-DC boost converter for ultra-low-power internet of things (IoT) applications operating with RF energy harvesting is proposed. A DC-DC boost converter is needed to boost the low output voltage of the RF energy harvester to provide a high voltage to the load. However, a boost converter operating at a low voltage supplied by ambient RF energy harvesting has a problem in that power conversion efficiency is significantly lowered. The proposed on-chip capacitive DC-DC boost converter simultaneously applies gate bias boosting and dynamic body biasing techniques using only the internal boosted voltage without an additional circuit that increases power loss to boost the voltage, achieving high efficiency at an input voltage as low as 0.1 V. The designed capacitive boost converter achieves a peak power conversion efficiency (PCE) of 33.8% at a very low input voltage of 0.1 V, a 14% improvement over the peak PCE of the conventional cross-coupled charge pump. A maximum peak PCE of 80.1% is achieved at an input voltage of 200 mV and a load current of 3 μA. The proposed capacitive boost converter is implemented with a total flying capacitance of 60 pF, suitable for on-chip integration.